Posterior ankle impingement syndrome in the tennis player - Maquirriain, J. (2002)
Pain in the posterior ankle can result from many causes and may represent a diagnostic challenge. Posterior ankle impingement syndrome refers to a group of pathologic entities that result from repetitive or acute foot plantar flexion. The talus and surrounding soft tissues are compressed between the tibia and the calcaneus, resulting in bone and/or soft tissue lesions. Several movement patterns during tennis play may produce such entities. Athletes complain of posterior ankle pain and limited and painful foot plantar flexion. Posterior ankle impingement syndrome aetiology includes postero-lateral talus process pathology, flexor hallucis longus tenosinovitis and capsular injuries. Although radiography and scintigraphy may offer relevant data, magnetic resonance imaging (MRI) clearly depicts the bone and soft tissues abnormalities associated with posterior ankle impingement syndrome. Different therapeutic options are available, including endoscopic surgery. 'We consider posterior ankle impingement syndrome as a valid initial clinical approach, but establishing a definitive diagnosis is essential in order to ensure the correct treatment', Dr. Maquirriain said.